INTERNALISASI NILAI-NILAI TASAWUF DALAM MENCEGAH PERILAKU BULLYING DI PONDOK PESANTREN ASH HABUL YAMIN LASI TUO - Shinta Gita Zahara; Salmi Wati; Wedra Aprison; Mustafa, Mustafa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Bullying remains a persistent problem in educational settings, including Islamic educational institutions such as pesantren. This phenomenon reflects a gap between the normative Islamic values taught and the social practices of students in their daily interactions. This study aims to analyze the process of internalizing Sufism values and their role in preventing bullying behavior at Pondok Pesantren Ashhabul Yamin Lasi Tuo. This research employs a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation involving pesantren leaders, teachers, and students as research participants. Data analysis was conducted using a descriptive-analytical method through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that Sufism values such as patience, sincerity, humility, self-control, and compassion have been normatively taught through religious instruction and spiritual guidance. However, these values have not been fully internalized in students’ daily behavior, as indications of bullying—particularly verbal and social forms—are still found in informal interactions. This study concludes that Sufism holds significant potential as a preventive approach to bullying in pesantren environments, yet its effectiveness depends on the strengthening of role modeling, behavioral habituation, continuous supervision, and the integration of Sufism values into the overall pesantren educational system.